'State Sponsored Cruelty': children in immigration detention - Jon Burnett (Medical Justice, 2010)
This report presents the findings of the first large-scale exploration, in the UK, of the physical and psychological harms caused and aggravated by the detention of children for immigrationpurposes. This incorporates medical and legal evidence, testimonies from detainees and ex-detainees, and other associated information. The medical evidence used in this report comes from the work of 15 independent expert clinicians.